Logic of Sense. Martin Urmann’s study of Fin-de-Siècle art between Paris and Vienna (KULT_online, 2016)
In his book Dekadenz. Oberfläche und Tiefe in der Kunst um 1900 Martin Urmann puts a seemingly well-known period of European cultural history into a surprising and at the same time essential perspective. The comparatist study consciously transcends disciplinary borders and shows the Décadence to be an epoch as much as aesthetics, exerting primary influence on 20th-century thought and perception. Combining historical depth with philosophical speculation, the study brings out new aspects of the Fin de Siècle in Paris and Vienna.